Earthquake early warning system - Nazri Wong, Mohammad Syakir; Abdul Rahim, Ruzairi; Abas, Khairul Hamimah; Manaf, Muhammad Shukri (Penerbit UTHM, 2020)
As the climate undergoes changes, the number of natural disasters increase and the severity of these occurrences increases over time. As the population of human race increases, natural protective terrains and barriers were destroyed for urbanization due to the exploitation of vulnerable areas on the earth. Earthquakes are unpredictable and as an initiative to adapt to climate changes and as a strategy to reduce earthquake disaster risk, early warning systems (EWS) has been internationally recognized to play a role in providing alerts to the public so that safety precaution procedures and protocols can be implemented in response to earthquake occurrences...